Composition and clinical impact of the immunologic tumor microenvironment in oral squamous cell carcinoma - Boxberg, Melanie; Weichert, Wilko (The journal of immunology, 2019)
Immunotherapy shows promising results and revolutionizes treatment of oral squamous cell carcinoma (OSCC). The immunologic microenvironment might have prognostic/predictive implications. Morphologic immunologic parameters (inflammatory infiltrate, stromal content, and budding activity [BA] [potentially indicating epithelial-mesenchymal transition]) were evaluated in 66 human primary therapy-naive OSCCs. Intraepithelial/stromal tumor-infiltrating lymphocytes (TILs; CD3+/CD4+/CD8+/CD4+FOXP3+/IL-17A+) were quantified, and ratios were calculated. HLA class I in tumor cells was evaluated immunohistochemically. mRNA in situ hybridization to detect IFN-γ was performed. Analysis was performed within invasive front (IF) and tumor center (TCe). Decreased HLA expression was associated with low TIL density, pronounced stromal content, and high BA; IFN-γ in TILs was correlated with high-density TILs; and IFN-γ in tumor cells was correlated with absence of BA (p < 0.05). Heterogeneity of parameters (TCe/IF) was rare. Low density of stromal CD4+FOXP3+ TILs within TCe and IF was identified as an independent prognostic factor for poor overall, disease-specific, and disease-free survival (p ≤ 0.011). Refining prognostication in OSCC with high-density CD4+FOXP3+ infiltrate within TCe and/or IF, high FOXP3:CD4 ratio was significantly correlated with favorable outcome in this subgroup. Furthermore, high-stromal CD8:CD4 ratio was found to be an independent favorable prognostic factor. In summary, immunologic parameters were closely intertwined. Morphologic correlates of epithelial-mesenchymal transition were associated with downregulation of HLA and decreased inflammation. Heterogeneity was infrequent. Low-density stromal CD4+FOXP3+ infiltrate within TCe and IF was an independent poor prognostic factor. Stratification of cases with high-density CD4+FOXP3+ TILs by FOXP3:CD4 ratio enables refinement of prognostication of this subgroup. CD8:CD4 ratio was identified as an independent prognostic factor.
Prepublished online 10 December 2018
Gesehen am 07.08.2019